Violence and the body : race, gender, and the state - Aldama, Arturo J., 1964- (Indiana University Press, 2003)
Violence and the Body: Race, Gender, and the State explores the relationship between subalternity, the discourse and technology of the body, and the rise and proliferation of racial, colonial, sexual, domestic, and state violence, examining the materiality of violence on the "otherized" body. Grounded in U.S./Mexico border and Latin American cultural studies, the essays in this collection intersect discussions of subalternity, violence, and discourses of the body in a transethnic, feminist, and global cul.